The relationship between cigarette smoking and the tongue microbiome in an East Asian population. Issue 1 (1st January 2020) - Sato, Noriaki; Kakuta, Masanori; Uchino, Eiichiro; Hasegawa, Takanori; Kojima, Ryosuke; Kobayashi, Wataru; Sawada, Kaori; Tamura, Yoshihiro; Tokuda, Itoyo; Imoto, Seiya; Nakaji, Shigeyuki; Murashita, Koichi; et al.
ABSTRACT: Background : The oral microbiome, which consists of various habitats, has been shown to be influenced by smoking. However, differences in the tongue microbiomes of current and former smokers, as well as their resultant functional consequences, have rarely been investigated in East Asian populations. Methods : We used 16S rRNA amplicon sequencing of tongue-coating samples obtained from East Asian subjects who were current, former, or never smokers to identify differences in their tongue microbiomes and related metagenomic functions. Two sets of participants from 2016 to 2017 (n = 657 and n = 187, respectively) were analyzed separately. Results : We found significant differences between the overall microbiome compositions of current versus never smokers (p = 0.0015), but not between former versus never smokers (p = 0.43) based on the weighted UniFrac distance. Twenty-nine of 43 investigated genera showed significantly different expression levels in current versus never smokers. Neisseria and Capnocytophaga were less abundant, and Streptococcus and Megasphaera were more abundant in current smokers. Moreover, the abundances of metagenomic pathways, including those related to nitrate reduction and the tricarboxylic acid cycle, were significantly different between current and never smokers. Conclusions : The tongue microbiomes and related metagenomic pathways of current smokers differ from those of never smokers among East Asians.